Progress towards bioinspired multicontrollable and multifunctional metasurfaces - Kumar P.; Lakhtakia A.; Jain P.K.; Rai S.; Bhattacharyya S. (My University, 2025)
We have designed multicontrollable and multifunctional metasurfaces comprising pixelated meta-atoms. Optimal tricontrollable metasurfaces comprising graphene-patched pixels for electrical control and InSb-patched pixels for thermal and magnetic control were designed to function either as terahertz absorbers or terahertz stopband filters. Clearly, these devices can also serve as trifunctional sensors. A single-pixel graphene-sandwich meta- atom was designed to function as a reciprocal switch, a stopband, a frequency shifter, and an isolator for the terahertz spectral regime. Such multicontrollable and multifunctional metasurfaces could be incorporated in diverse products, thereby reducing inventory costs, enhancing repairability and product lifetimes, and promoting standardization. © COPYRIGHT SPIE. Downloading of the abstract is permitted for personal use only.